Nanomaterials for liver cancer targeting: research progress and future prospects - Xu, Jiahong; Liu, Yefu (Frontiers in Immunology, 2025)
The incidence and mortality rates of liver cancer in China remain elevated. Although early-stage liver cancer is amenable to surgical resection, a significant proportion of patients are diagnosed at advanced stages. Currently, in addition to surgical resection for hepatocellular carcinoma, the primary treatment modalities predominantly include chemotherapy. The widespread use of chemotherapy, which non-selectively targets both malignant and healthy cells, often results in substantial immunosuppression. Simultaneously, the accumulation of chemotherapeutic agents can readily induce drug resistance upon reaching the physiological threshold, thereby diminishing the efficacy of these treatments. Besides chemotherapy, there exist targeted therapy, immunotherapy and other therapeutic approaches. Nevertheless, the development of drug resistance remains an inevitable challenge. To address these challenges, we turn to nanomedicine, an emerging and widely utilized discipline that significantly influences medical imaging, antimicrobial strategies, drug delivery systems, and other related areas. Stable and safe nanomaterials serve as effective carriers for delivering anticancer drugs. They enhance the precision of drug targeting, improve bioavailability, and minimize damage to healthy cells. This review focuses on common nanomaterial carriers used in hepatocellular carcinoma (HCC) treatment over the past five years. The following is a summary of the three drugs: Sorafenib, Gefitinib, and lenvatinib. Each drug employs distinct nanomaterial delivery systems, which result in varying levels of bioavailability, drug release rates, and therapeutic efficacy.